2018
DOI: 10.1038/s41598-018-36087-8
|View full text |Cite
|
Sign up to set email alerts
|

Figure-ground perception in the awake mouse and neuronal activity elicited by figure-ground stimuli in primary visual cortex

Abstract: Figure-ground segregation is the process by which the visual system identifies image elements of figures and segregates them from the background. Previous studies examined figure-ground segregation in the visual cortex of monkeys where figures elicit stronger neuronal responses than backgrounds. It was demonstrated in anesthetized mice that neurons in the primary visual cortex (V1) of mice are sensitive to orientation contrast, but it is unknown whether mice can perceptually segregate figures from a background… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 46 publications
10
51
0
Order By: Relevance
“…This result is in line with our main finding that illusory colour can only be decoded at the second superficial depth. It also matches previous findings that edges between figure and ground selectively activate layer 2/3 in non-human primates( 50 ) and mice( 51 ). However, it is not in line with Kok’s et al’s conclusions that illusory perception selectively involves deep layers.…”
Section: Supplementary Figuressupporting
confidence: 91%
“…This result is in line with our main finding that illusory colour can only be decoded at the second superficial depth. It also matches previous findings that edges between figure and ground selectively activate layer 2/3 in non-human primates( 50 ) and mice( 51 ). However, it is not in line with Kok’s et al’s conclusions that illusory perception selectively involves deep layers.…”
Section: Supplementary Figuressupporting
confidence: 91%
“…Contextual modulation represents a fundamental computation to extract meaning from visual scenes. It could support many perceptual phenomena, such as pop-out effects, figure-ground segregation, detection of borders, and object detection (Angelucci et al, 2017;Bergen and Julesz, 1983;Jones et al, 2001;Kapadia et al, 2000;Knierim and van Essen, 1992;Lamme, 1995;Rossi et al, 2001;Schnabel et al, 2018;Seriès et al, 2003;Treisman and Gelade, 1980). Furthermore, the dichotomy between surround suppression and cross-orientation facilitation is consistent with a predictive processing framework (Bastos et al, 2012;Keller and Mrsic-Flogel, 2018;Rao and Ballard, 1999).…”
Section: Discussionmentioning
confidence: 58%
“…Consistent with perceptual phenomena, the stimulus evoked responses of neurons are modulated by the surround. This contextual modulation occurs at several stages of the visual system including the retina (Alitto and Usrey, 2008;Chiao and Masland, 2003;Huang et al, 2019;McIlwain, 1964;Ölveczky et al, 2003;Solomon, 2006), the thalamus (Alitto and Usrey, 2008;Jones et al, 2012Jones et al, , 2015Levick et al, 1972), and the visual cortex (Alexander and Van Leeuwen, 2010;Angelucci et al, 2017;Fitzpatrick, 2000;Kapadia et al, 2000;Knierim and van Essen, 1992;Rossi et al, 2001;Schnabel et al, 2018;Slllito et al, 1995) progressively increasing the complexity of the contextualized spatial features.…”
Section: Introductionmentioning
confidence: 99%
“…In the visual system, these feedforward pathways define the classical feedforward receptive field (ffRF), the area in space where visual stimuli excite a neuron 1 . The visual system also uses visual context, the visual scene surrounding a stimulus, to predict the content of the stimulus 2 , and accordingly, neurons have been found that are excited by stimuli outside their ffRF 38 . The mechanisms generating excitation to stimuli outside the ffRF are, however, unclear.…”
mentioning
confidence: 99%
“…Through this antagonism, neurons respond when a stimulus is presented in either the fbRF or ffRF but not in both together, effectively performing an exclusive-OR operation. Suppression of responses to stimuli in the ffRF by surrounding stimuli is a well-established phenomenon that enables neurons to report boundaries by detecting differences in stimulus features between the excited region inside the ffRF and their surround 7, 8, 14, 15, 2831 . Our results show that neurons with an excitatory fbRF report differences in stimulus features regardless of whether the excited region is located inside or outside the ffRF.…”
mentioning
confidence: 99%